Sub Distribution Panel’s Design Rancangan SubDistribution Panel: Rancangan Desain Panel Sub Distribusi Rancangan Panel Sub Distribusi - Nanggala, Dikas Pandu; Ahfas, Akhmad (Procedia of Engineering and Life Science, 2024)
Electrical panels play an important role as the center of electrical energy distribution, functioning to regulate the flow of electricity in a building. This distribution process requires something that can secure and divide the amount of power flowing, therefore the SDP (Sub Distribution Panel) panel is needed. This panel contains several components that are assembled into one unit so that it can function properly. This research uses a qualitative descriptive method that focuses on problems based on facts carried out by means of observation or observation, interviews, and studying documents. If all the techniques in this method are performed successfully, the accurate percentage of this research is 98%. This research produces a description of the process of making SDP panels from start to finish. This research resulted that the SDP panel has several functions, namely collecting and forwarding power to each load in each branch as needed, connecting and disconnecting the power distribution circuit and the safety of the power distribution system control.